Analysis of the "Jasmine" Segment in "Turandot" - Li, Luxingyu (Journal of Social Science and Humanities, 2024)
"Jasmine" is known as China's second national anthem. At the beginning of the 20th century, it was used as a representative of "China" by Puccini's opera "Turandot". This paper takes it as a perspective to analyze the "Jasmine" segment in "Turandot," knowing how the song has been adapted in its "return from abroad."